2023
DOI: 10.1038/s41392-022-01264-9
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA-sequencing reveals radiochemotherapy-induced innate immune activation and MHC-II upregulation in cervical cancer

Abstract: Radiochemotherapy (RCT) is a powerful treatment for cervical cancer, which affects not only malignant cells but also the immune and stromal compartments of the tumor. Understanding the remodeling of the local ecosystem induced by RCT would provide valuable insights into improving treatment strategies for cervical cancer. In this study, we applied single-cell RNA-sequencing to paired pre- and post-RCT tumor biopsies from patients with cervical cancer and adjacent normal cervical tissues. We found that the resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…Although Hirotaka et al found that dietary consumption of Lactobacillus-derived exopolysaccharide induced CCR6 + CD8 + T cells by CCL20-secreting tumor cells [ 56 ], Wang et al also uncovered FOXO1 promoted the migration of M2 macrophages via CCL20 secretion in esophageal squamous cell carcinoma [ 57 ]. Besides, resently Liu et alrevealed a specific M2-like macrophages subtype with high CCL20 expression, which is associated with worse prognosis by single-cell analysis in CESC [ 58 ]. Besides, they proposed that CCL20 + macrrophges also expressed high levels of CXCL8, which is in accordance with our PPI analysis in TCGA-CESC as well [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although Hirotaka et al found that dietary consumption of Lactobacillus-derived exopolysaccharide induced CCR6 + CD8 + T cells by CCL20-secreting tumor cells [ 56 ], Wang et al also uncovered FOXO1 promoted the migration of M2 macrophages via CCL20 secretion in esophageal squamous cell carcinoma [ 57 ]. Besides, resently Liu et alrevealed a specific M2-like macrophages subtype with high CCL20 expression, which is associated with worse prognosis by single-cell analysis in CESC [ 58 ]. Besides, they proposed that CCL20 + macrrophges also expressed high levels of CXCL8, which is in accordance with our PPI analysis in TCGA-CESC as well [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…GO analysis demonstrated that the interleukin cytokines were the major molecular event altered in TA/Fu‐TS inhibiting inflammation (Figure 5E). [ 20 ] Therefore, TA/Fu‐TS could promote the macrophage phenotype‐switching, and inhibit inflammation by interleukin‐related pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Specific subpopulations of cervical cancer, such as the HPV-reprogrammed keratinocyte subpopulation, were identified to provide evidence for tumor virus infection and cancer evolution 29 . The radiochemotherapy-induced innate immune activation and MHC-II upregulation in cervical cancer was also revealed by scRNA-seq 30 . Single-cell dissection of T cell subpopulation in cervical cancer tissues showed that targeting IDO1 and immune checkpoint inhibitors could improve the therapeutic efficacy 31 .…”
Section: Discussionmentioning
confidence: 99%